PENGARUH INTERVAL PENYIRAMAN DAN KONSENTRASI PAKLOBUTRAZOL TERHADAP PERTUMBUHAN GENERATIF TANAMAN KEDELAI (Glycine max L. Merill) PADA TANAH ULTISOL - Yusuf Sabilu; Rita Ningsih; Wa Ode Hasnia (BioWallacea : Jurnal Penelitian Biologi (Journal of Biological Research), 2015)
ABSTRACTThe purpose of this study was to knew 1) influence watering intervals towards generative growth of soybean (Glycine max L. Meriil) on Ultisol soil, 2) influence paclobutrazol concentrate towards generative growth of soybean (Glycine max L. Meriil) on Ultisol soil, 3) interaction between watering intervals and concentration paklobutrazol towards generative growth of soybean ( Glycine max L. Merrill ) on the ultisol soil. This research is an experimental factorial design using RAL (Complete Randomized Design) with two treatments: watering intervals (Once time in a day, once time in two days, once time in three days) and paclobutrazol (0 ppm, 100 ppm, 200 ppm) with three replications. Growth parameters measured were generative growth include early flowering plant, total of pods, total of seeds, seed weight and carcass weight. Data were analyzed by ANOVA and followed by Tukey's test. The results was showed that an own treatment of watering intervals did not significantly to affect toward early flowering but significant effect on the total of pods, total of seeds, seed weight and carcass weight. Paclobutrazol treatment significantly to delay the onset of flowering and decrease the number of pods, number of seeds, seed weight and carcass weight. The interaction between the both were not significantly affected all of these parameters. Tukey test results showed that the watering interval once time in two days the most optimum conditions to result pods, total of seeds, seed weight and carcass weight soybean plants. Paclobutrazol treatment without giving the best results to accelerate early flowering and increase the total of pods, total of seeds, seed weight and carcass weight compared with paclobutrazol treatment.Keywords : Watering interval, Paclobutrazol, Generative growth, Soybean, Ultisol soil